Correlation between clinical disease activity and interferon-γ autoantibody titers measured by inhibitory ELISA, and inflammatory biomarkers in adult-onset immunodeficiency associated with anti-interferon-γ autoantibodies - Putthapon Teepapan; Apinya Chungcharoenpanich; Kanokkarn Pinyopornpanish; Supa Oncham; Prawat Chantharit; Porpon Rotjanapan; Wannada Laisuan (PLoS ONE, 2026)
Background Anti-interferon-γ autoantibodies (Anti-IFN-γ AAbs) contribute to immunodeficiency and increase susceptibility to intracellular infections, particularly in adults. Measurement of anti-IFN-γ AAb titers using inhibitory ELISA is a valuable diagnostic tool for adult-onset immunodeficiency. However, the relationship between inhibitory ELISA titers, inflammatory biomarkers, and clinical disease activity remains unclear. Methods This retrospective study analyzed 69 blood samples from 39 patients with detectable anti-IFN-γ AAbs at Ramathibodi Hospital. Data collected included demographics, clinical disease activity, and laboratory biomarkers such as white blood cell (WBC) count, interleukin-6 (IL-6), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and inhibitory ELISA titers. Disease activity was categorized as active or in remission based on clinical evaluation and the status of infection. Results The mean patient age was 58.38 ± 8.55 years, and 61.5% were female. Anti-IFN-γ AAb titers had an area under the receiver operating characteristic curve (AUC) of 0.893. A cut-off of 1:50,000 (50% inhibition) yielded 92.90% specificity in determining active disease status. Median titers were significantly higher in active disease (1:100,000, interquartile range [IQR]: 1:10,000–1:100,000) compared with remission (1:5,000, IQR: 1:5,000–1:10,000, p < 0.001). Combining anti-IFN-γ AAb titers (≥ 1:50,000) with ESR (≥ 45 mm/hr), CRP (≥ 18 mg/dL), WBC (≥ 10,455 cells/µL), and IL-6 (≥ 16 pg/mL) further improved the prediction of disease activity (AUC = 0.903, sensitivity = 88.9%, specificity = 91.7%). Conclusions High anti-IFN-γ AAb titers correlate with active disease, and inhibitory ELISA may aid in disease monitoring. Combining IFN-γ AAbs titers with inflammatory biomarkers may improve predictive accuracy.